2017
DOI: 10.1016/j.neuropsychologia.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity-based constraints on category-specificity in the ventral object processing pathway

Abstract: Recent efforts to characterize visual object representations in the ventral object processing pathway in the human brain have led to contrasting proposals about the causes of neural specificity for different categories. Here we use multivariate techniques in a novel way to relate patterns of functional connectivity to patterns of stimulus preferences. Stimulus preferences were measured throughout the ventral stream to tools, animals, faces and places; separately, we measured the strength of functional connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 78 publications
10
52
2
Order By: Relevance
“…Voxels in lateral occipitotemporal cortex respond to images of hands (Orlov et al, 2010) and tools (Bracci et al, 2012), and exhibit functional connectivity to the left inferior parietal lobule (Bracci et al, 2012;Mahon et al, 2007). Furthermore, parietal disconnection extended to ventral temporal cortex to include the fusiform gyrus, consistent with prior functional connectivity findings in apraxia (Watson et al, 2019) and in neurotypical adults (Garcea & Mahon, 2014; see also Chen et al, 2017;Stevens et al, 2015). In light of these findings, it has been argued that the processing of object properties in ventral temporal cortex provides an input to the praxis system, because the extraction of visual attributes of objects (e.g., whether an object is slippery, hot, or sharp) as well as stored knowledge of material properties (e.g., object weight; Gallivan et al, 2014) informs the retrieval of hand posture and deployment of an object-directed grasp when functionally manipulating a tool for discussion, see Gallivan & Culham, 2015).…”
Section: Implications For Neurocognitive Models Of Praxis In the Humasupporting
confidence: 81%
“…Voxels in lateral occipitotemporal cortex respond to images of hands (Orlov et al, 2010) and tools (Bracci et al, 2012), and exhibit functional connectivity to the left inferior parietal lobule (Bracci et al, 2012;Mahon et al, 2007). Furthermore, parietal disconnection extended to ventral temporal cortex to include the fusiform gyrus, consistent with prior functional connectivity findings in apraxia (Watson et al, 2019) and in neurotypical adults (Garcea & Mahon, 2014; see also Chen et al, 2017;Stevens et al, 2015). In light of these findings, it has been argued that the processing of object properties in ventral temporal cortex provides an input to the praxis system, because the extraction of visual attributes of objects (e.g., whether an object is slippery, hot, or sharp) as well as stored knowledge of material properties (e.g., object weight; Gallivan et al, 2014) informs the retrieval of hand posture and deployment of an object-directed grasp when functionally manipulating a tool for discussion, see Gallivan & Culham, 2015).…”
Section: Implications For Neurocognitive Models Of Praxis In the Humasupporting
confidence: 81%
“…A number of fMRI studies have demonstrated there is a high degree of cross-talk between the dorsal and ventral visual pathways as a function of grasping or generating tool-directed gestures (e.g., see Budisavljevic, Dell'Acqua, & Castiello, 2018;Garcea et al, 2018;Hutchison & Gallivan, 2018) or when viewing objects or making judgments about object manipulation (e.g., Chen, Snow, Culham, & Goodale, 2018;Chen et al, 2017;Freud, Rosenthal, Ganel, & Avidan, 2015;Kleineberg et al, 2018;Sim, Helbig, Graf, & Kiefer, 2015; for discussion, see Orban & Caruana, 2014;van Polanen & Davare, 2015). Our results offer a novel interpretation of the role that the left SMG plays in tool-directed actions: Tool manipulation knowledge is not "represented" in the left SMG; rather the left SMG sits at the nexus of the dorso-dorsal and ventro-dorsal visual pathways, and serves as an intermediary or "hub" region aggregating (a) representations of object properties and conceptual knowledge in the ventral stream with (b) online sensory-motor information processed in the dorsal stream, (c) which is informed by top-down biasing signals from prefrontal cortex to resolve competition between candidate tool use actions.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the scan, careful training and instruction was given to participants to pantomime tool use and tool transport actions. The training procedure was identical to previous training instructions we have administered to participants (e.g., Chen et al, , ; Chen, Garcea, et al, ; Erdogan, Chen, Garcea, Mahon, & Jacobs, ; Garcea et al, ) in which participants are trained to generate a gesture as if the tool stimulus was “in‐hand.” Importantly, because participants are in a physically constrained environment in the bore of the magnet, they were instructed to generate gestures at a slow rate (∼1 gesture per second) for the duration of the event; because there was no visual feedback during scanning (i.e., each participant's right hand was out of sight during the scan), the experimenter ensured that the participants memorized the tool transport and tool use actions prior to the scan by asking them to generate each action from memory. During each run the experimenter visually inspected the participant's gesturing action in real time to verify that the participants were generating actions when cued by the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has also shown that voxel-wise resting FC in visual cortex is better approximated by the FC evoked by movies than by more artificial stimuli such as rotating checkerboards or static pictures of stimuli (Strappini et al 2018, Wilf et al 2017. Finally, Chen and colleagues (Chen et al 2017) measured the voxelwise resting FC between regions of ventral visual cortex and a second region that was functionally related to a specific visual category (e.g. tools).…”
Section: Introductionmentioning
confidence: 99%
“…This analysis bears some resemblance to a representational similarity analysis, which is a standard methodology for identifying the representational content of evoked activity in a brain region (Kriegeskorte et al 2008). Unlike Chen et al (Chen et al 2017), we examine the multi-vertex pattern of resting activity at each timepoint rather than separately analyzing each individual vertex over timepoints in a resting FC analysis.…”
Section: Introductionmentioning
confidence: 99%